ANALISIS OPTIMALISASI KOMANDO PENYELAM DAN PENYELAMATAN BAWAH AIR KOARMADA RI GUNA MENDUKUNG TUGAS TNI - Natsir Dimyati; Wahyudin Arif; Untung Tarmanto (UJoST- Universal Journal of Science and Technology, 2023)
Security and sovereignty in these waters have a very important role in maintaining the integrity of the state. Therefore, the Indonesian Navy (TNI AL) as one of the components of national defense plays a major role in protecting and maintaining the sovereignty of Indonesia's maritime territory. One of the elements that supports the role of the Indonesian Navy in securing Indonesian waters is the Indonesian Navy's Underwater Diving and Rescue Command (Koppeba). Koppeba has special responsibility in carrying out underwater diving and rescue operations covering a wide range of missions, including search and rescue, maintenance and repair of underwater infrastructure, as well as monitoring and protection activities of national assets in and around Indonesian waters. This research aims to conduct an analysis of the optimization of the Indonesian Navy's Underwater Diving and Rescue Command (Koppeba) in supporting the duties of the Indonesian Navy (TNI AL). The use of the NVivo application is used to collect, organize and analyze data related to Koppeba's role in the context of maritime defense. This research explores the extent to which Koppeba can be increased in supporting the Indonesian Navy's operations in Indonesian waters. The research method involves document analysis, interviews and surveys which are then analyzed using NVivo to identify patterns, trends and opportunities in an effort to optimize Koppeba's role. The results of this research highlight several recommendations for increasing Koppeba's role in supporting the Indonesian Navy, including improving training and equipment, development of cross-agency collaboration, as well as the use of advanced technology in diver operations and underwater rescue. This research provides valuable insight for stakeholders in efforts to strengthen Indonesia's maritime defense capabilities through optimizing Koppeba Koarmada.